Vegetation and Climate of Maritime Canada 6000 Years BP: A Synthesis - Jetté, Hélène; Mott, Robert (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1995)
ABSTRACTEnvironmental conditions (vegetation and climate) of Maritime Canada are reconstructed as a regional contribution to a national synthesis on the paleoenvironment of Canada 6000 yr BP. Ten new sites, including three complete sequences and seven short sequences bracketing the 6 ka period, are added to the existing pollen dataset for this region. The vegetation prevalent 6000 yr BP in New Brunswick was a mixed coniferous-deciduous forest with pine, mostly white pine (Pinus strobus) in the northwest, and a mixed coniferous-deciduous forest with hemlock (Tsuga canadensis) in the south and southeast. In the northwest, fir (Abies) replaced pine at high elevations and a boreal forest grew on the New Brunswick Highlands. The dominant vegetation at 6000 yr BP in Prince Edward Island and Nova Scotia was a mixed coniferous-deciduous forest with hemlock dominating. Cape Breton Island was covered by a mixed coniferous-deciduous forest with pine and/or fir, except for the southern part of the Island where hemlock was probably present. Analysis of the fossil sites indicate that a warm-dry period influenced the composition of the vegetation 6000 yr BP.